Aliran Kebatinan: Analisis Pemikiran Hamka Terhadap Sejarah Kebatinan Dan Singkretisme Agama Di Indonesia - Erwin, Erwin; Saputra, Edriagus (Institut Agama Islam Sumatera Barat Pariaman, 2023)
This research uses qualitative methods in the form of library research. Data is explored through primary and secondary sources. Primary sources were obtained through Hamka's writings about kebatinan and secondary sources were obtained through articles published in accredited journals and books related to the theme of this article. The data analysis technique uses the content analysis method. The content analysis method allows the data in the writing to be discussed objectively and systematically to describe Hamka's thoughts about mysticism. The results of this research can be concluded that Hamka as a Muslim figure (Mufassir) and national hero, of course Hamka's views on public beliefs in Indonesia have a strong academic basis. As a devout religious person, Hamka has the toughness and intelligence of monotheism which has been tested throughout the history of his life, but on the other hand, Hamka realizes that syncretism is a proven fact in the daily lives of religious communities in Indonesia